Association of Apolipoprotein C3 Levels and Hepatic Steatosis: A Follow-Up Study - Heinz, Patrick; Boehm, Bernhard Otto; Schmidberger, Julian; Kratzer, Wolfgang; for the EMIL-Study Group; Wolfgang Kratzer (Hormone and Metabolic Research, 2020)
Apolipoprotein C3 is a lipid-binding protein with a pivotal role in triglyceride metabolism and inflammation. This 11-year follow-up study aimed to evaluate apolipoprotein C3 levels and other parameters as markers of hepatic steatosis, in a random, population-based cohort in southern Germany. In 2013, we selected and re-examined 406 study participants (193 women, 213 men; average age 58.1±11.3 years) from the original “Echinococcus multilocularis and other internal diseases in Leutkirch I“ (EMIL I) cohort studied in 2002. All participants received upper abdominal sonography to grade potential hepatic steatosis, and blood tests to determine apolipoprotein C3 levels and other laboratory parameters. Body mass index, waist-to-hip ratio, and anthropometric measures were documented. The follow-up study conducted in 2013 included a partial correlation analysis. We found an association between hepatic steatosis and elevated apolipoprotein C3 levels (p<0.0001). Study participants with a novel diagnosis of hepatic steatosis had the highest apolipoprotein C3 serum levels (p=0.0002). Hepatic steatosis was associated with low levels of high density lipoprotein cholesterol (p=0.0374), high levels of total cholesterol (p=0.0117), increased homeostasis model assessment of insulin resistance (p=0.0002), elevated alanine transaminase (p<0.0001), elevated aspartate transaminase (p=0.0003), and elevated C-reactive protein (p=0.0446). Apolipoprotein C3 serum levels were associated with the presence, disease grade, and new development of hepatic steatosis likewise to biomarkers of the metabolic syndrome.
Keywords: apolipoprotein C3; hepatic steatosis; liver enzymes; inflammatory markers; cross-sectional study